2004
DOI: 10.1111/j.1523-1755.2004.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric acute renal failure in southwestern Nigeria

Abstract: These results show that many of the causes of ARF in our patients are preventable; it should be possible to reduce morbidity due to ARF through purposive preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
100
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 13 publications
17
100
7
Order By: Relevance
“…By contrast, options for RRT in pediatric AKI in many parts of sub-Saharan Africa are limited (1)(2)(3)(4). Although continuous RRT is commonly used in the management of pediatric AKI in resourcerich countries, and although it may have some advantages in the hemodynamically unstable patient, it is rarely used in the management of AKI in many parts of sub-Saharan Africa because it is expensive and requires both sophisticated technology and consumables that are generally unavailable (5).…”
mentioning
confidence: 99%
“…By contrast, options for RRT in pediatric AKI in many parts of sub-Saharan Africa are limited (1)(2)(3)(4). Although continuous RRT is commonly used in the management of pediatric AKI in resourcerich countries, and although it may have some advantages in the hemodynamically unstable patient, it is rarely used in the management of AKI in many parts of sub-Saharan Africa because it is expensive and requires both sophisticated technology and consumables that are generally unavailable (5).…”
mentioning
confidence: 99%
“…The proportion of cases of acute renal failure that correspond to acute postinfectious glomerulonephritis of demonstrated or assumed poststreptococcal etiology is 13% in New Delhi, 44 30% in Istanbul, 45 51.6% in Casablanca, 46 4.6% in Lagos, 47 27% in Bombay, 48 19.2% in Lucknow, 49 33% in Asunció n, 50 17.4% in Chandrigarth, 51 5.2% in Lima, 52 9.3% in Varanasi, 53 and 25% in Osun State, Nigeria. 54 …”
mentioning
confidence: 99%
“…Olowo et al 22 found higher incidence of HUS and glomerulonephritis. Many of the cases with ARF were secondary to Burkitt's lymphoma.…”
Section: Comparison With Nephrotic Syndrome In Elderlymentioning
confidence: 99%